PENGARUH PEMBELAJARAN SENSOMOTORIK DAN PENDEKATAN PEMBELAJARAN BAHASA TERHADAP PERKEMBANGNA KOGNITIF ANAK USIA 5-6 Tahun di PAUD : Penelitian ini memanfaatkan pendekatan kuantitatif dan menggunakan desain eksperimen faktorial 2×2. - Evi wati; Ida Ermiana; Darmiany Darmiany (STKIP Subang, 2025)
Learning in formal Early Childhood Education (PAUD) settings still tends to focus partially on cognitive outcomes, while motor and language stimulation has not yet been well integrated. This study aims to examine how sociomotor learning and language learning approaches influence the cognitive development of children aged five to six years in formal PAUD Class B, with age treated as a control variable. The study employed a quantitative approach using a 2×2 factorial experimental design, and the data were analyzed using Analysis of Covariance (ANCOVA). The results indicate that both the language learning approach and sociomotor learning have a significant effect on children’s cognitive development (p < 0.05). However, there is no evidence of a simultaneous effect of the two variables on the cognitive development of children aged five to six years. These findings emphasize the importance of holistic and integrated learning in early childhood education.